Xanthophyll-cycle of ice algae on the sea ice bottom in Saroma Ko lagoon, Hokkaido, Japan - Kudoh, Sakae; Imura, Satoshi; Kashino, Yasuhiro (National Institute of Polar Research, 2003)
P(論文) Using the ice algal community prevailing on the sea ice bottom in Saroma Ko lagoon, Hokkaido, Japan, the response of a photosynthetic system to exposure to light was investigated, focusing on xanthophylls-cycle features, diel changes of the pool size of xanthophylls-cycle pigments and the effective quantum yield of PS II in early February, 1998. By pigment analysis, β-carotene, chlorophylls a and c, diadinoxanthin, diatoxanthin and fucoxanthin were detected as major pigments, which suggests that diatoms dominated as ice algae during this study. When such ice algae were exposed to irradiance nearly 4 times higher than the daily maximum level at the ice bottom, the interconversion between diadinoxanthin and diatoxanthin continued for ca. 20 min immediately after the onset of irradiation in spite of the sub-zero Celsius ambient temperature. Although the pool size of this xanthophylls-cycle (relative amount of diadinoxanthin plus diatoxanthin per chlorophyll a) was not so large compared to that of mesophilic diatoms, it showed a circadian change increasing during the daytime and decreasing at night. This change correlated well with the effective quantum yield of PS II. These results suggest that ice algae at the sea ice bottom possess a relatively effective xanthophylls-cycle to regulate light energy usage. However, the xanthophylls-cycle in ice algae may be poor compared to that of algae living in intermediate irradiance, which can be interpreted from the point of view of bioenergetic aspects of shade adapted ice algae. departmental bulletin paper